PBL Berbantuan Aplikasi Clinometer dalam Upaya Peningkatan Motivasi Belajar - Mayangsari, Sizillia Noranda (FKIP Universitas Wisnuwardhana, 2024)
The focus of this study was to conduct classroom action research in two cycles, with the objective of enhancing and categorizing student learning motivation as high. The specific aim of this research was to explore the utilization of the Problem-Based Learning (PBL) model, supported by the clinometer application, in order to elevate the learning motivation of class X-2 students at SMA Negeri 6 Malang. Problem Based Learning is an innovative approach to education that involves the integration of technology, specifically the clinometer application, to facilitate a deeper understanding of the subject matter. Additionally, the success of this model relies on the teacher's ability to effectively and inspirationally convey the material. Data collection techniques use observation sheets, questionnaires, and interviews which are then analyzed quantitatively. The main challenge faced by mathematics teachers is how to increase students' learning motivation, especially in material that is considered complex and abstract, such as trigonometry. In the initial cycle, the research findings indicated that the students' average level of motivation for learning was categorized as low, standing at 52%. However, in the subsequent cycle, this average surged to 71%, falling within the high category. This demonstrates a notable increase of 19% in the students' overall learning motivation.